The Effect of Spiritual Fortitude on Mental Health Symptoms Amidst the COVID-19 Pandemic - Zhang, Hansong; Aten, Jamie D.; Coomes, Steven P.; Davis, Cameron W.; Davis, Don E.; Hodge, Adam S. ca. 20./21. Jh.; Hook, Joshua N.; Karwoski, Logan T.; Van Tongeren, Daryl R. (2020)
The COVID-19 pandemic is a global traumatic stressor affecting millions of individuals worldwide. Traumatic events often cause significant resource loss and negatively affect mental health and emotional well-being. In the wake of trauma, many people draw on religious or spiritual faith to cope with adversity and suffering. One construct that has received increased attention within the field of religious/spiritual coping is spiritual fortitude (SF), which is one's ability to consistently draw on spiritual and religious resources to cope with negative emotions in the face of stressors (Van Tongeren et al., 2018). In this paper, we present data from 255 participants who completed measures of resource loss related to the ongoing COVID-19 pandemic, SF, depression, anxiety, and post-traumatic stress disorder (PTSD) symptoms. SF buffered the deleterious relationship between resource loss and mental health symptoms. Specifically, for individuals high in SF, the relationship between resource loss and mental health symptoms was weaker than for individuals low in SF. We conclude by discussing limitations of the current study, areas for future research, and implications for practice.
Keywords: Covid-19 Pandemic; Emotions; Mental Health; Post-traumatic stress disorder; PSYCHOLOGICAL adaptation; Symptoms